ANALISIS SERVICE QUALITY DAN CUSTOMER PERCEIVED VALUE TERHADAP CUSTOMER SATISFACTION MELALUI CUSTOMER TRUST SEBAGAI VARIABEL MEDIASI - Martin Sihombing; Dessy Kurnia Sari; Donard Games (Journal Publicuho, 2023)
This research aims to see the influence of service quality and customer perceived value on customer satisfaction through customer trust as a mediating variable at BPJS Employment Padang Branch Office. The population is all BPJS Employment Padang Branch Office participants. The sample criteria is that they have submitted a guarantee claim within the last 6 months. The number of samples in the study was 160 respondents. Hypothesis testing uses one-tailed statistical analysis, the hypothesis is accepted if the t-statistic value is > 1.65 and the significance value is < 0.05. The research results show that service quality and customer perceived value have a significant positive effect on customer trust, and service quality and customer trust have a significant positive effect on customer satisfaction. Meanwhile, customer-perceived value does not affect customer satisfaction. Indirectly, service quality and customer perceived value influence customer satisfaction with customer trust as the mediation.